Students’ Perspectives towards Innovation of Technology in Teaching and Learning of Language - Nor Shahila Mansor; Hazlina Abdul Halim; Normaliza Abd Rahim (Indonesian Journal of EFL and Linguistics, 2017)
This study provides a discussion of the innovations, in particular students’ perspectives towards the use of technology in teaching and learning. The study aimed to (1) identify methods of teaching and learning that can be applied in the classroom to engage students, (2) to determine factors in selecting the methods of teaching and learning by respondents. The data of this study were collected through questionnaire. The respondents of the study consisted of 150 undergraduate students from various programs aged between 19 and 23 at Universiti Putra Malaysia. The race or ethnicity of the respondents is disregarded as it is irrelevant to the objectives of the study. The results were presented in qualitative and quantitative. From 7 types or options of technological innovation listed, all of the respondents (100%) tend to prefer the use of various media as well as computer-assisted teaching as innovations in teaching and learning. Meanwhile, a total of 139 respondents (93%) prefer the use of overhead projector and the use of VCD in the classroom. 123 students (82%) choose the video teleconferencing approach, 113 students (75%) choose the use of interactive video and 90 of the respondents (60%) favour the use of printed media such as advertisements in newspapers, magazines and etc. In line with the development of technology, innovation in teaching and learning is viewed as a prerequisite in optimizing the output of education. This study also shows to the importance of the innovation to ensuring the continuity of education.